Hubungan Motivasi Kerja dengan Hasil Penilaian Kerja Karyawan dalam Perspektif Manajemen - Dinda Bastari; Sarah Georetty Manullang; Melsa Amanda; Merika Setiawati (CV. ITTC INDONESIA, 2025)
This article seeks to explore the connection between work motivation and employee performance appraisal outcomes from a managerial psychology perspective through an in-depth review of the literature. The study adopts a library research approach by analyzing relevant academic journals, books, and recent scholarly publications. The review reveals that work motivation significantly influences employee attitudes and work behavior, which in turn affects performance evaluation results. Employees with stronger motivation tend to demonstrate higher commitment in achieving organizational performance targets. The study concludes that work motivation and performance appraisal function as interrelated managerial elements that require continuous and integrated management to enhance overall human resource performance..